Valuasi Sifat Fisik Batuan di Kawasan Karst Maros Pangkep Taman Nasional Bantimurung Bulusaraung - Muhammad Arsyad; Mardianti Rukmana; Pariabti Palloan (Jurnal Penelitian Pendidikan IPA, 2022)
This research is an experimental study that aims to analyze and valuate the physical properties of rocks in the Maros Pangkep Karst Area. The samples were 60 (sixty) consisted of each 30 (thirty) samples in the Maros Karst Area (04°58'-05°01' S and 119°39'-119°41' E) and in the Pangkep Karst Area (04°51'-04°53' S and 119°37'-119°38' E). The analysis results of the physical properties of rocks in the Maros Karst Area obtained modified limestone and dolomite limestone with density values in the range of 1.50-2.68 g/cm3 and porosity of 0-50%, indicating secondary porosity. The Pangkep Karst Area obtained dolomite limestone with density values of 2.47-2.65 g/cm3 and porosity of 0-5%, indicating primary porosity. There are differences in physical properties of rock in the Maros Karst Area and Pangkep Karst Area based on an independent sample t-test. The valuation of the physical properties of rocks in the Maros Karst Area have special quality (5-50%), sufficient quality (10-15%), poor quality (5-10%), and negligible quality (0-5%) and in the Pangkep Karst Area has negligible quality (0-5%). Based on this valuation, karst rocks in the Maros Karst Area can be recommended reservoar and karst rocks in the Pangkep Karst Area can be recommended as aggregate limestone.